Probabilidade de insolvência das empresas que compõem o Índice de Sustentabilidade Empresarial (ISE) e das demais listadas na BM&FBovespa no período de 2006 a 2011 - Moraes, Luis Fernando Salles (2012)
The current economic scenery, with high competition level among market players, easy access to economic and financial information and increasing number of companies that went bankrupt in recent years, changed the investors behavior and the decisive factors of investment targets. Nowadays, to mitigate these risks, shareholders became more concerned to long-term analysis and in this context arise the new concept of socially responsible companies, those that are sustainable and profitable to shareholders, even though this idea is also shared by BM&FBovespa it is not supported by current researches. This research aims to compare the probability of insolvency of corporations that make up the Corporate Sustainability Index (ISE) and others traded on BM&FBovespa. The research was done in two different moments: model creation and model application to a controlled group. The model used the insolvent and solvent companies from 2006 up to 2011 and established annual equations to calculate the probability of insolvency. Applying the model it was possible to identify the corporations probability of insolvency that belong to the ISE. The results of this study allowed to confirm based on the average probability of insolvency that ISE´s companies have less default chances if compared with sector correspondents traded in the stock market.